2017
DOI: 10.1177/1060028017697424
|View full text |Cite
|
Sign up to set email alerts
|

Selexipag, an Oral Prostacyclin-Receptor Agonist for Pulmonary Arterial Hypertension

Abstract: The specific role of selexipag for managing PAH patients is unclear because of its modest efficacy, lack of mortality reduction, and cost similar to intravenous prostacyclins. Additional clinical trials exploring combination therapy as well as its role in other types of pulmonary hypertension are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Expression of IP and PPARγ decreases in the pulmonary arteries of patients with PAH, compared with unaffected individuals (Ameshima et al, 2003 ; Falcetti et al, 2010 ), and this effect was also demonstrated in our rat HPH model. Analogs of prostacyclin and agonists of IP have been used successfully in the treatment of patients with PAH (Leuchte et al, 2003 ; Baker et al, 2017 ). Activation of PPARγ exerts anti-proliferative, anti-thrombotic, and vasodilatory effects on the vasculature in PAH, and agonists of PPARγ have efficacy in the treatment of animal models of PAH (Green et al, 2011 ; Liu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of IP and PPARγ decreases in the pulmonary arteries of patients with PAH, compared with unaffected individuals (Ameshima et al, 2003 ; Falcetti et al, 2010 ), and this effect was also demonstrated in our rat HPH model. Analogs of prostacyclin and agonists of IP have been used successfully in the treatment of patients with PAH (Leuchte et al, 2003 ; Baker et al, 2017 ). Activation of PPARγ exerts anti-proliferative, anti-thrombotic, and vasodilatory effects on the vasculature in PAH, and agonists of PPARγ have efficacy in the treatment of animal models of PAH (Green et al, 2011 ; Liu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Селексипаг представляет собой пролекарство, которое гидролизуется в печени с образованием активного метаболита MRE-269, обладающего свойствами высокоселективного агониста IP-рецепторов. При проведении исследований на модели монокроталиновой легочной гипертензии препарат продемонстрировал способность улучшать функциональное состояние эндотелия сосудов легких, сдерживать гипертрофию / гиперплазию гладкомышечных клеток средней оболочки сосудов и гипертрофию правого желудочка, что в итоге сопровождалось улучшением выживаемости экспериментальных животных [11]. Благодаря высокой функциональной селективности, селексипаг и его метаболит не оказывали стимулирующее действие на гладкие мышцы желудка, что позволило минимизировать такие характерные для простаноидов побочные эффекты, как тошнота и рвота.…”
Section: результатыunclassified
“…The efficacy of selexipag was seen by improvements in pulmonary hemodynamics, exercise capacity, and clinical symptoms in a cohort of adult Japanese PAH patients [6]. More detailed discussion and information about selexipag use in adult PAH can be found in several recent reviews [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%